Sensory And Affective As Antecedents Repurchase Intention Of Pucuk Harum Tea Customers In Cimahi - Ariq Nasharullah; Yadi Ernawadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research examines the factors that influence the repurchase intention of Pucuk Harum Tea consumers in Cimahi. One hundred twenty respondents who had experience consuming Pucuk Harum Tea were involved as primary data sources in this research. A cross-sectional method was used to collect data. Meanwhile, the research instrument in the form of a questionnaire has been declared to have passed the convergent validity, discriminant validity, and composite reliability tests. The data analysis technique used is structural equation modelling (SEM) using the Smart-PLS version 3.0 tool. For the seven proposed research hypotheses, five are supported by empirical data. The findings of this study show that sensory has a direct effect on repurchase intention. Meanwhile, affective influence both directly and indirectly on repurchase intention. It is hoped that the results of this research will provide benefits for further study and the objects being assessed regarding designing strategies relevant to improving the quality of sensory and affective attributes. Future researchers are advised to explore other factors that can influence repurchase intention.